ABOUT THE POSSIBILITY OF USING THE RED SLADGE IN THE SYNTHESIS OF INORGANIC PIGMENTS COFFE-BROWN COLOUR - Ivanyuk, E.V.; Suprunchuk, V.I. (Sworld-Us Conference proceedings, 2023)
It is investigated the conditions for the formation of chromophore compounds when using red sludge, a waste product of alumina production. It is shown that in the presence of SiO2 and Na2O, the synthesis temperature decreases, which can be seen on the de